Vibrationally resolved in situ XPS study of activated adsorption of methane on Pt(111) - Fuhrmann, Thomas; Kinne, Martin; Whelan, Caroline; Zhu, Junfa; Denecke, Reinhard; Steinrück, Hans-Peter (Chemical Physics Letters, 2004)
A combination of high-resolution X-ray photoelectron spectroscopy at BESSY II and molecular beam techniques has been used to investigate the dissociative adsorption of CH and CD on a Pt(111) surface. From a detailed analysis of C 1s core-level spectra, CH (CD ) has been identified as the adsorbed species at 120 K, independent of the kinetic energy of the impinging methane molecules (in the range from 0.25 to 0.83 eV). The spectra show a unique fine structure, caused by vibrational excitations of C-H (C-D) stretching modes in the photoemission process. Using temperature-programmed XPS, CH is identified as the intermediate in the dehydrogenation process, forming at 260 K and further dehydrogenating to carbon above 500 K. © 2004 Elsevier B.V. All rights reserved.